2022
DOI: 10.1021/acs.langmuir.2c00648
|View full text |Cite
|
Sign up to set email alerts
|

Amyloids Formed by Nonaromatic Amino Acid Methionine and Its Cross with Phenylalanine Significantly Affects Phospholipid Vesicle Membrane: An Insight into Hypermethioninemia Disorder

Abstract: The incorrect metabolic breakdown of the nonaromatic amino acid methionine (Met) leads to the disorder called hypermethioninemia via an unknown mechanism. To understand the molecular level pathogenesis of this disorder, we prepared a DMPC lipid membrane, the mimicking setup of the cell membrane, and explored the effect of the millimolar level of Met on it. We found that Met forms toxic fibrillar aggregates that disrupt the rigidity of the membrane bilayer, and increases the dynamic response of water molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 76 publications
(261 reference statements)
1
43
0
Order By: Relevance
“…This could be linked to returning back to the same local environment around ACYMAN in the EV system. Next, to gain a better understanding of LMW-HA-induced flexibility/rigidity on HA-EVs, we performed fluorescence anisotropy. The faster component (φ1) (equation S1) was attributed to the local motion of the probe molecule (ACYMAN), whereas the longer nanosecond component (φ2) carried the information regarding the segmental motion of the ACYMAN as it is inside the EVs. After Hyals treatment to the LMW-HA-EVs, time-resolved fluorescence anisotropy of ACYMAN on EVs (average rotational time scale, ⟨τr⟩ ≈ 1910 ps) became significantly retarded compared to that of the LMW-HA-EVs (average rotational time scale, ⟨τr⟩ ≈ 1440 ps) (Table ) (insets of Figure ) (Table S1).…”
mentioning
confidence: 81%
“…This could be linked to returning back to the same local environment around ACYMAN in the EV system. Next, to gain a better understanding of LMW-HA-induced flexibility/rigidity on HA-EVs, we performed fluorescence anisotropy. The faster component (φ1) (equation S1) was attributed to the local motion of the probe molecule (ACYMAN), whereas the longer nanosecond component (φ2) carried the information regarding the segmental motion of the ACYMAN as it is inside the EVs. After Hyals treatment to the LMW-HA-EVs, time-resolved fluorescence anisotropy of ACYMAN on EVs (average rotational time scale, ⟨τr⟩ ≈ 1910 ps) became significantly retarded compared to that of the LMW-HA-EVs (average rotational time scale, ⟨τr⟩ ≈ 1440 ps) (Table ) (insets of Figure ) (Table S1).…”
mentioning
confidence: 81%
“…Later studies demonstrated that these phenomena are not unique to phenylalanine but are shared among metabolites in general. Proteinogenic and non‐proteinogenic amino acids, nucleobases, various metabolic intermediates, and even sphingolipids were shown to form ordered amyloid‐like assemblies with structural and biological properties similar to those observed for phenylalanine structures [9, 16–28] . The formed assemblies also show clear biological and chemical properties as observed for phenylalanine‐ and protein‐based amyloid fibrils.…”
Section: Metabolite Self‐assembly: An Extension Of the Amyloid Hypoth...mentioning
confidence: 66%
“…Proteinogenic and non-proteinogenic amino acids, nucleobases, various metabolic intermediates, and even sphingolipids were shown to form ordered amyloid-like assemblies with structural and biological properties similar to those observed for phenylalanine structures. [9,[16][17][18][19][20][21][22][23][24][25][26][27][28] The formed assemblies also show clear biological and chemical properties as observed for phenylalanine-and protein-based amyloid fibrils. These include nano-scale morphology, dyebinding properties, and apoptosis-inducing activity.…”
Section: Metabolite Self-assembly: An Extension Of the Amyloid Hypoth...mentioning
confidence: 68%
See 2 more Smart Citations